Sustainable Design: Building-Integrated Photovoltaic on Residential House Envelopes - Saeed Hussein Alhmoud; Husam Hussein Alhmoud; Ejeng Bassey Ukabi (Journal of Studies in Science and Engineering)
This research investigates the integration and optimization of Building Integrated Photovoltaic (BIPV) systems on residential rooftops in Amman, Jordan—an area experiencing rapid urbanization and high solar potential. The study aims to identify the most effective orientations and azimuth angles for maximizing solar energy generation during both summer and winter seasons. Solar radiation data was analyzed using a case study on Haneen Bin Isaac Street using PVGIS and Autodesk Ecotect Analysis tools. The methodology simulated insolation values on south-facing and south-eastern/south-western rooftop surfaces at different azimuth angles (120°, 135°, and 150°) and tilt configurations. The results demonstrate that south-eastern and south-western orientations yield higher solar gain during winter, especially at 135° and 150°. Southern orientations perform efficiently across all examined angles during summer, with only slight variation. These findings support the strategic application of BIPV in residential architecture, enhancing energy efficiency while maintaining design quality. The study concludes with practical design recommendations for architects and urban planners to incorporate BIPV as an active element in sustainable construction. The outcomes also provide a framework for broader regional application in similar climatic and urban contexts.